Clinical Results of Immunoscintigraphy in a Variety of Malignant Tumors with Special Reference to Immunohistochemistry - Biersack, H. J.; Bockisch, A.; Oehr, P.; Knoblich, A.; Hartlapp, J.; Biltz, H.; Jaeger, N.; Bellmann, O.; Vogel, J.; Björklund, B.; Taylor-Papadimitriou, J.; Winkler, C. (Nuklearmedizin - NuclearMedicine, 1986)
Radioimmunoscintigraphy was performed in 52 patients with a variety of malignant tumors (colorectal, melanoma, lung, testicular, ovarian, bladder, carcinoid). Respective antibodies or their F(ab’)2 fragments against CEA (n = 23), melanoma antigen 225.28 S (n = 18), TPA (n = 4), ßHCG (n = 5) and HMFG2 (n = 2) were selected by immunohistochemistry of the primary tumor. Most patients were suspected of recurrence or of hitherto unknown distant or local metastases. Overall accuracy was 61 % (32/52). False negatives amounted to 33% (17/52). Useful additional clinical information – not available by CT, ultrasonics or serum levels of tumor markers – was obtained in 17 out of 52 patients (= 33%). From these results it seems obvious that antibodies used for radioimmunoscintigraphy should be selected on the basis of immunohistochemistry.Bei 52 Patienten mit unterschiedlichen malignen Tumoren (Kolorektal, Melanom, Hoden, Ovar, Blase, Karzinoid, Lunge) wurde eine Radioimmunszintigraphie durchgeführt. Die entsprechenden Antikörper oder deren F(ab’)2-Fragmente gegen CEA (n = 23), Melanomantigen 225.28 S (n = 18), TPA (n = 4), ßHCG (n = 5) und HMFG2 (n = 2) wurden anhand immunhistochemischer Untersuchungen des Primärtumors ausgewählt. Bei allen Patienten bestand der Verdacht auf ein Rezidiv oder bislang unbekannte Lokal- oder Fernmetastasen. Die Treffsicherheit betrug 61% (32/ 52). Falsch negative Befunde wurden in 17 von 52 Fällen festgestellt (33%). Zusätzliche wichtige klinische Informationen, die weder durch CT, Ultraschall oder erhöhte Serumwerte für Tumormarker zu erhalten waren, konnten in 33% der Fälle gewonnen werden. Diese Ergebnisse machen deutlich, daß vor Durchführung der Radioimmunszintigraphie zur Suche nach Rezidiven oder Metastasen entsprechende Tumorantikörper anhand immunhistochemischer Untersuchungen des Primärtumors ausgewählt werden sollten.